Falafel Nation : Cuisine and the Making of National Identity in Israel - Raviv, Yael (Book collections on Project MUSE., 2015)
"Examines the role of food in the construction of the Jewish nation, using food from field to table as a lens through which to understand Israeli history, society, and politics"--